THE ROLE OF MOZE GAMES TO THE ABILITY OF RECONGNIZING NUMBER SYIMBOL OF GROUP B TK HANDAYANI BALIASE - Fitriana; Nurfitra (Education Journal, 2021)
This research is about Maze games to the ability of recognizing number syimbol of Group B TK Handayani Baliase. This descriptive qualitative research involved 15 children consisted of 7 boys and 8 girls. Data were collected through 1) observation sheet, 2) interview, 3) documentation; and were analyzing using percentage technique. Average recapitulation result in the first week shows that 6% well developed, 13.33% develop as expected,31.10% begin to develop,48.88% undeveloped, second week reveals 11.11% well developed, 26.66% develop as expected, 31.11% begin to develop, and 24.44% undeveloped, the third week shows 35.45% well develop 50% develop as expected, 15.5% begin to develop, and 6.66% undeveloped is aspect of mention numbers, sort numbers, and group the same number. Therefore, it can be concluded that Maze games affects the ability of recognizing number syimbol of Group B TK Handayami Baliase